2020
DOI: 10.3892/etm.2020.8525
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin�D supplementation on polycystic ovary syndrome: A meta‑analysis

Abstract: The aim of the present meta-analysis was to evaluate the effect of vitamin D supplementation on patients with polycystic ovary syndrome (PCOS). A literature search was performed to identify all of the relevant studies comparing the effect of vitamin D supplementation with placebo in PCOS patients, in the PubMed, Embase and Web of Science databases. All statistical analyses were performed on case-control studies using Review Manager 5.3 software, provided by the Cochrane Collaboration. A total of 11 studies inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 33 publications
1
48
0
5
Order By: Relevance
“…Additionally, vitamin D deficiency may be a risk factor in the development of this endocrine-metabolic pathology [41]. A meta-analysis of 11 RCTs that included 483 patients with PCOS evaluated the effect of vitamin D supplementation versus placebo [42]. The group treated with vitamin D supplements showed a reduction in insulin resistance and TC versus the placebo group.…”
Section: Vitamin D's Action On Lipid Profilementioning
confidence: 99%
“…Additionally, vitamin D deficiency may be a risk factor in the development of this endocrine-metabolic pathology [41]. A meta-analysis of 11 RCTs that included 483 patients with PCOS evaluated the effect of vitamin D supplementation versus placebo [42]. The group treated with vitamin D supplements showed a reduction in insulin resistance and TC versus the placebo group.…”
Section: Vitamin D's Action On Lipid Profilementioning
confidence: 99%
“…Their results were comparable to our study, except that TG levels were also significantly improved (−11.88 mg/dL; 95% CI: −17.03, to −6.73, I 2 = 0%) in our study, which is similar to the results of previous RCTs 13 16 and meta-analyses. 7 , 22 , 23 In Miao et al.’s study, 34 only post-treatment levels were evaluated when comparing the VitD intervention with placebo. Their results showed a marginally non-significant effect of VitD on TG (−5.59 mg/dL; 95% CI: −12.11 to 0.93, I 2 = 0%).…”
Section: Discussionmentioning
confidence: 99%
“…Another common finding in PCOS and obesity is vitamin D deficiency (VDD) that has been reported to increase the risk of systemic infections and to impair immune response [ 38 , 39 ]. Conversely, vitamin D supplementation can prevent respiratory infections through several immunoregulatory functions including the decreased production of pro-inflammatory cytokines by innate immune system, therefore reducing the risk of cytokine storm leading to pneumonia [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies have demonstrated that VDD might be a causal factor in the pathogenesis of IR and the metabolic syndrome in PCOS [ 40 ]. Indeed, a relatively high prevalence of VDD is observed among women with PCOS (approximately 67–85 % PCOS women) and compared with the general population, the prevalence of VDD is relatively higher in PCOS patients [ 38 ]. Additionally, positive associations of VDD with some well-known comorbidities of PCOS including T2DM, IR, metabolic syndrome, and cardiovascular diseases, are reported [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation